Menjaga Mutu Pendidikan di Tengah Pandemi Covid-19: Studi Pembelajaran Online di Universitas Islam Negeri Walisongo Semarang - Kurnia Muhajarah; Silvia Riskha Fabriar (Unversitas Muhammadiyah Mataram, 2020)
Abstract: Various efforts have been made by the Government in collaboration with universities to reduce the spread of Covid-19 in the campus environment. Rector of Walisongo Islamic State University Semarang has also responded to the government's instruction, one of which is by implementing online learning. This research is a descriptive qualitative study that aims to obtain an overview of online learning during the Covid-19 pandemic at the Faculty of Da'wa and Communication. Data is collected through the Google Form. Data analysis was performed usinginteractive analysis techniques Miles & Huberman. The results showed that onlinelearning made students feel more comfortable to ask questions and express their opinions compared to face-to-face lectures. The effectiveness of online learning was related to the availability of internet services and low-cost e-learning platforms. This is evidenced by the Whatsapp Group (WAG) platform that ranks first, followed by Line, Google Classroom, Google Meet, Zoom,then platforms other than this, and Webex ranks last.Abstrak: Berbagai usaha dilakukan Pemerintah bekerjasama dengan perguruan tinggi demi mengurangi penyebaran Covid-19 di lingkungan kampus. Rektor UIN Walisongo Semarang menanggapi himbauan Pemerintah, salah satunya dengan melaksanakan pembelajaran online. Penelitian ini merupakan penelitian kualitatif deskriptif yang bertujuan untuk memperoleh gambaran pembelajaran online masa pandemi Covid-19 di Fakultas Dakwah dan Komunikasi,.Data dikumpulkan melalui aplikasi Google Form. Analisis data dilakukan menggunakan teknik analisis interaktif Miles & Huberman. Hasil penelitian menunjukkan bahwa pembelajaran online membuat mahasiswa merasa lebih nyaman untuk bertanya dan mengemukakan pendapatnya dibanding perkuliahan tatap muka, Efektivitas pembelajaran online berkaitan dengan ketersediaan layanan internet dan platform e-learning berbiaya rendah. Hal ini terbukti dengan platform Whatsapp Group (WAG) menempati urutan pertama diikuti Line, Google Classroom, Google Meet, Zoom, kemudian platform selain ini, dan Webex menempati urutan terakhir.